Transformasi Strategi Pengadaan Fasilitas Belajar untuk Mendukung PJJ pada Masa Pandemi di Pesantren Mahasiswa Teknologi Informasi dan Komunikasi Depok - Agnesya Wulantika; Dudun Ubaedullah (Universitas Darunnajah Jakarta, Indonesia, 2023)
Over the past year, the educational landscape has undergone significant shifts in response to the global pandemic. Limitations on physical interaction and efforts to reduce the spread of the virus have compelled educational institutions to transition to a Distance Learning (DL) model. This study focuses on the transformation of procurement strategies for learning facilities to support DL during the pandemic. A qualitative method was utilized, taking a case study approach in five leading educational institutions in Indonesia.The findings indicate that there are three main factors that are the focal points in procuring learning facilities for DL: technology, accessibility, and quality of learning materials. Technology serves as the backbone of DL, but its provision must be balanced with equitable accessibility for all students. Therefore, procurement strategies involve collaborations with technology service providers, the government, and the community to ensure every student has access to learning tools. Moreover, the quality of learning materials also becomes pivotal, given the dynamics of DL which require curriculum and teaching method adjustments.This research recommends that educational institutions consider cross-sectoral partnerships in their procurement strategies and ensure adequate training for educators in using the new learning facilities. Through this procurement strategy transformation, it is hoped that education can remain effective and inclusive amidst the pandemic challenges.